INDEXQUAL: A CONCEPTUAL MODEL OF INDIVIDUALLY EXPERIENCED QUALITY OF LONG-TERM CARE. (11th November 2018) - Sion, K; Haex, R; Verbeek, H; De Boer, B; Zwakhalen, S; Odekerken-Schröder, G; Schols, J; Hamers, J
Abstract: Aim: The aim of this research was to develop a conceptual model presenting elements that influence the experienced quality of long-term care (LTC) as perceived by individual care recipients. It can be used to gain a better understanding of experienced quality in the LTC sector. Method: A scoping review was performed to identify definitions and models of quality from an individual's perspective in the health care and business sector. Results: Findings of the scoping review revealed information that enabled the development of a draft model on experienced quality of LTC: IndExQual. Quality of LTC from an individual perspective consists of a pre (expectations), a during (experiences), and a post (assessment) phase. Expectations are formed prior to an experience by means of personal needs, prior experiences and word-of-mouth. Hereafter an experience occurs, which is greatly influenced by caring relationships in line with relationship-centred care. Especially in LTC, relationships are an important aspect of an experience, because the main aim is not to cure clients but to care for them. After the experience an evaluation occurs of what happened and how it happened (perceived quality), and how this made the individual feel (satisfaction). Conclusion: IndExQual differs from existing models for several reasons. Whereas most experienced quality models focus solely on satisfaction as their outcome of experienced quality, this model incorporates perceived quality as well. Additionally, it places the care relationships at the centre of the quality experience; and, it portrays the gap between an experience and the evaluation of that experience.